784 views
2 votes
H(x) = x2 + 1 k(x) = x – 2

Evaluate 3h(2) + 2k(3) =

User Wwkudu
by
5.4k points

2 Answers

4 votes

5, 9, and 17

Explanation:

User Jesus David
by
5.6k points
0 votes

Answer:

17

Explanation:


h(x) =x^2 +1\\k(x)=x-2\\\\3h(2)+2k(3)\\\\h(2)= ?\\k(3)=?\\\\h(2) = (2)^2 +1\\= 4+1\\h(2)=5\\\\\\k(3)= 3-2\\k(3) = 1\\\\3h(2) +2k(3)\\\\= 3(5)+2(1)\\=15+2\\3h(2)+2k(3) = 17

User CrepeGoat
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.